2018
DOI: 10.1097/md.0000000000009880
|View full text |Cite
|
Sign up to set email alerts
|

Argininemia as a cause of severe chronic stunting and partial growth hormone deficiency (PGHD)

Abstract: Rationale:Argininemia is an autosomal recessive inherited disorder of the urea cycle. Because of its atypical symptoms in early age, diagnosis can be delayed until the typical chronic manifestations – including spastic diplegia, deterioration in cognitive function, and epilepsy – appear in later childhood.Patient concerns:A Chinese boy initially presented with severe stunting and partial growth hormone deficiency (PGHD) at 3 years old and was initially treated with growth hormone replacement therapy. Seven yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Currently, it is characterized by scissors gait. Cai et al [ 10 ] reported a case of peripheral nerve damage, demonstrating it is one of the neurologic impairments of argininemia. In our patient, a peripheral nerve examination revealed mildly reduced MCV of bilateral tibial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is characterized by scissors gait. Cai et al [ 10 ] reported a case of peripheral nerve damage, demonstrating it is one of the neurologic impairments of argininemia. In our patient, a peripheral nerve examination revealed mildly reduced MCV of bilateral tibial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Adult-onset cases have also been reported [25,26]. During early childhood (3 months-4 years), patients may be of short stature and exhibit clumsiness, psychomotor impairment, loss of developmental milestones, global developmental delay, and regression after initial normal neurodevelopment [27,28]. Loss of bowel and bladder control can also occur [29].…”
Section: Clinical Manifestations and Physical Historymentioning
confidence: 99%
“…2,4,13 ARG1-D can be misdiagnosed as other neurological diseases such as cerebral palsy or hereditary spastic paraplegia due to similarities in clinical presentation. 3,14 Delays in diagnosis of ARG1-D are also common. 15,16 These delays are largely due to a lack of disease awareness combined with the variability in disease manifestation.…”
Section: Introductionmentioning
confidence: 99%
“…ARG1‐D can be misdiagnosed as other neurological diseases such as cerebral palsy or hereditary spastic paraplegia due to similarities in clinical presentation 3,14 . Delays in diagnosis of ARG1‐D are also common 15,16 .…”
Section: Introductionmentioning
confidence: 99%